The Theme of a Female Militant (on the Material of B. Vasilyev’s Novel «The Dawns Here Are Quiet») - Abdo Дина Мухамед (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This work is devoted to the theme of a woman fighter and discusses the characteristics of different motives associated with this topic. To achieve our goal, we will touch upon Boris Vasilyev’s novel “The Dawns Here Are Quiet” to trace the reflection of such motives characteristic of the topic, based on the critical-literary and descriptive-analytical methods that correspond to the purpose and objective of the study. As a result, we have the following conclusions: the literature of the Great Patriotic War is divided into two stages: the first stage is the literature of the war period, and the second is the literature of the postwar period. – Boris Vasilyev’s creativity belongs to the second stage of military literature, which was formed within one of the literary trends of the anti-Stalinist movement – military prose. He is one of the few writers who touched upon the little-talked-about subject of the woman-fighter. – In his novel “The Dawns Here Are Quiet” Vasilyev truthfully portrayed a woman in the war, the dramatic conflict of everyday life through the image of five young girls – anti-aircraft gunners. It embodies the characteristics of the military theme in connection with the theme of women fighters, sound motives of patriotism, fear, description of the female body, motherhood and murder. – The writer used some artistic means by which he was able to portray the images of his heroines, their characters, thoughts, feelings, relationships and destiny. Among the tools used are portrait, comparison, figurative antithesis, dialogue and others.